Seymour/Carraher’s polymer chemistry - Carraher, Charles E. (CRC Press, 2008)
This introductory text surveys the scientific, engineering, technology, and commercial aspects of polymer science. Emphasizing the fundamental behavior of polymers reflected in current technological developments, this seventh edition contains new chapters on composites, fibers, and naturally occurring polymers in plants and animals. It also highlights nanoscale polymer applications, with new material on drug discovery and design, electronics, optical fibers, textiles, biodegradable materials, smart materials, and adhesives. Listings of common polymer structures, nomenclature and trade names, and Internet resources have been updated and expanded for this edition. Learning features include chapter summaries, study tips, glossaries, and exercises with solutions. The text will be used to teach graduate and undergraduate courses in departments of chemistry, chemical engineering, and materials sciences, and for teaching polymer science and technology in polymer science institutes.